School Culture In Elementary School Elementary School 2 Tamanasri Kec. Pringkuku, Kab. Pacitan, East Java - Zuyyina Fihayati; Sevilinda Ayu Arisma; Tri Utami; Isnaini Siti Fatimah; Anisa Setiawati (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study examines the role of school culture in influencing students' character building, learning motivation, and academic achievement. School culture encompasses values, norms, traditions, and habits shared by students, teachers, and staff within the school environment. A qualitative approach with a case study method was employed at SDN 2 Tamanasri, located in Tamanasri Village, Pringkuku Sub-district, Pacitan Regency. Data collection methods included observations, in-depth interviews with teachers and students, and document analysis of school activities. The findings reveal a positive school culture characterized by discipline, cooperation, and respect, reflected in daily routines and extracurricular programs. These activities enhance students' talents and foster stronger social bonds within the school. The study concludes that effective school culture management is crucial for creating a conducive learning environment and supporting students' holistic development. Future research should explore broader contexts to validate these findings and their applicability.